Моделювання об'єднання синхронних зон у процесі відновлення ОЕС України після особливої системної аварії - Кириленко, О.В.; Павловський, В.В.; Стелюк, А.О.; Баталов, А.Г. (Технічна електродинаміка, 2011)
The processes of synchronous area interconnection during the restoration of Interconnected power system (IPS) of Ukraine after blackout have been considered. By the example of the local node it’s shown that the interconnection of IPS of Russia and Belarus at substation 750 kV “Dneprovska􀉿a” improves the quality of the transients in IPS of Ukraine. The modeling results of dynamic modes of IPS of Russia and Belarus interconnection at Yuzhno-Ukrainskaia nuclear power plant and substation 750 kV “Dneprovskaia” are shown.